Chromosomal mosaicism in the fetoplacental unit. (July 2017) - Grati, Francesca Romana; Malvestiti, Francesca; Branca, Lara; Agrati, Cristina; Maggi, Federico; Simoni, Giuseppe
Abstract : Cytogenetic prenatal diagnosis on chorionic villi (CV) can be complicated by the detection of "chromosomal mosaicism." This is one of the main issues of first-trimester cytogenetic prenatal diagnosis as it can involve different types of chromosomal abnormalities, and the prediction of the fetal involvement is challenging because the detected abnormal mosaic cell line is not necessarily extended to fetal tissues. In addition, because the cell-free fetal DNA that is targeted by the new technologies for fetal aneuploidy risk assessment is mainly derived from the CV cells, the same challenges related to chromosomal mosaicism can be transferred into this new clinical field. This review illustrates the phenomenon of fetoplacental mosaicism, the management of prenatal diagnosis cases complicated by the detection of such a biological phenomenon, and the implications of its presence for the management of high-risk cfDNA testing results for fetal aneuploidies. Highlights: Fetoplacental chromosomal mosaicism is one of the main issues in the first-trimester cytogenetic prenatal diagnosis on CV. It has implications on the interpretation and management of cfDNA testing results. Provided risk figures can be utilized as guidance during the post-test counseling after the detection of a mosaicism in CV and during pre- and post-test cfDNA testing counseling.